Cardiovascular disease in HIV patients: from bench to bedside and backwards - Cerrato, Enrico (Open Heart, 2015)
HIV patients are exposed to a higher risk of adverse cardiovascular events, due to complex interactions between traditional risk factors and HIV infection itself in terms of ongoing endothelial dysfunctional immune activation/inflammation and increased risk of thrombosis. On the other hand, long-span antiretroviral therapy administration still raises questions on its long-term safety in an era in which life expectancy is becoming longer and longer while treatment of non-HIV-related serious events is increasingly raising concern. In this article, we will critically analyse the current knowledge of pathological and clinical aspects pertaining to the increased risk of cardiovascular events associated with HIV.